Overcoming the imatinib-resistant BCR-ABL mutants with new ureidobenzothiazole chemotypes endowed with potent and broad-spectrum anticancer activity - Ashraf K. El-Damasy; Heewon Jin; Jung Woo Park; Hyun Ji Kim; Hanan Khojah; Seon Hee Seo; Ju-Hyeon Lee; Eun-Kyoung Bang; Gyochang Keum (Taylor & Francis Group, 2023)
The design of kinase inhibitors targeting the oncogenic kinase BCR-ABL constitutes a promising paradigm for treating chronic myeloid leukaemia (CML). Nevertheless, the efficacy of imatinib, the first FDA-approved targeted therapy for CML, is curbed by the emergence of resistance. Herein, we report the identification of the 2-methoxyphenyl ureidobenzothiazole AK-HW-90 (2b) as a potent pan-BCR-ABL inhibitor against imatinib-resistant mutants, particularly T315I. A concise array of six compounds 2a-f was designed based on our previously reported benzothiazole lead AKE-5l to improve its BCR-ABLT315I inhibitory activity. Replacing the 6-oxypicolinamide moiety of AKE-5l with o-methoxyphenyl and changing the propyl spacer with phenyl afforded 2a and AK-HW-90 (2b) with IC50 values of 2.0 and 0.65 nM against BCR-ABLT315I, respectively. AK-HW-90 showed superior anticancer potency to imatinib against multiple cancer cells (NCI), including leukaemia K-562. The obtained outcomes offer AK-HW-90 as a promising candidate for the treatment of CML and other types of cancer.